Democratic crisis and global constitutional law / Christopher Thornhill, University of Manchester. - Thornhill, C. J. (Christopher J.), 1966- (Global law series., 2021)
Democratic Crisis and Global Constitutional Law explains the current weakness of democratic polities by examining antinomies in constitutional democracy and its theoretical foundations. This book argues that democracy is usually analysed in a theoretical lens that is not adequately sensitive to its historical origins. The author proposes a new sociological framework for understanding democracy and its constitutional preconditions, stressing the linkage between classical patterns of democratic citizenship and military processes and arguing that democratic stability at the national level relies on the formation of robust normative systems at the international level. On this basis, he argues that democracy is frequently exposed to crisis because the normative terms in which it is promoted and justified tend to simplify its nature. These terms create a legitimising space in which anti-democratic movements, typically with a populist emphasis, can take shape and flourish.